Wave 1 weighting and non-response - Lawrence, D; Misson, S; Johnstone, R; Soloff, C (My University, 2006)
This paper explains the methodology used to calculate the weights for the Wave 1 sample of the Longitudinal Study of Australian Children, which aims to examine the impact of Australia's social, economic and cultural environment on the next generation. The paper covers weighting principles, the study population, the Wave 1 response, design weights, the approach to non response analysis, the results, the outcome of weighting, weights in the Wave 1 dataset, standard errors and design effect, the accuracy of estimates, and non response from other study respondents.
3
Technical paper
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology